PRODUCTION OF EXPANDED POLYSTYRENE BASED ON LOCAL RAW MATERIALS (American Journal of Pedagogical and Educational Research, 2023)
In the subject of this article, the scientific and practical work on polystyrene concrete, the raw materials used for the production of polystyrene concrete and their properties were studied. Physico-mechanical and physico-chemical properties of polystyrene concrete were studied using research methods. Air-entrained polystyrene granules, vermiculite and thermal power plant ash waste were used as the main raw materials for the production of polystyrene concrete, thus the complex properties of polystyrene concrete were studied and the optimal composition was developed.